Liming and fertilisation in Pinus taeda plantations with severe nutrient deficiency in savanna soils (Acta Scientiarum. Agronomy, 2014)
Soils with high acidity and low exchangeable bases may be responsible for low yields of Pinus taeda in a forest plantation at Jaguariaíva, Paraná State, Brazil. The aim of this study was to evaluate the effect of liming and fertilisation, applied over litter, on two selected areas with Pinus taeda plantations. Soil, litter and pine needles were evaluated for K, Ca and Mg concentrations and soil acidity parameters. Seven treatments were applied: (i) complete (N, P, K, Zn, Cu, B, Mo, and lime); (ii) without N, P, and K; (iii) without Zn, Cu, B, and Mo; (iv) without K; (v) without Zn; (vi) without lime; and (vii) control (without nutrients and lime). Soil samples were collected at five soil depths (0-5, 5-10, 10-20, 20-40 and 40-60 cm) simultaneously with litter samples. Needles were also collected from the first and second pine flushes. Liming induced soil pH, Ca2+, and Mg2+ increases, and the opposite was observed for Al3+ and Al saturation. Fertilisation increased soil exchangeable K+ concentrations and needle and litter K concentrations. The low Ca and Mg concentrations found in the plant needles might be attributable to their low mobility.